2012
DOI: 10.1016/j.cub.2012.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Inactivation and Subsequent Heterochromatinization of a Centromere Stabilize Dicentric Chromosomes

Abstract: Chromosomes with multiple centromeres are stabilized by epigenetic centromere inactivation, which is initiated by kinetochore disassembly. Consequent heterochromatinization and histone deacetylation expanding from pericentric repeats to the central domain prevent reactivation of the inactivated centromere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 42 publications
3
75
1
Order By: Relevance
“…In fission yeast, Sato et al (136) have demonstrated that epigenetic inactivation is initiated by disassembly of kinetochore components. Mutations that compromise kinetochore protein promote centromere inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…In fission yeast, Sato et al (136) have demonstrated that epigenetic inactivation is initiated by disassembly of kinetochore components. Mutations that compromise kinetochore protein promote centromere inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Another illustration of epigenetic regulation in S. pombe is provided by the way that cells deal with dicentric chromosomes. One centromere in a dicentric chromosome can become inactivated because of disassembly of the kinetochore and the CENP-A chromatin and assembly of heterochromatin over the central domain (Sato et al 2012). Even in the absence of heterochromatin components, centromeric shutdown can occur by the assembly of a hypoacetylated chromatin state.…”
Section: Epigenetic Inheritance Of the Functional Centromere Statementioning
confidence: 99%
“…One is centromere inactivation through DNA rearrangements or epigenetic switches at one centromere (Lejeune et al 1973;Avarello et al 1992;Kramer et al 1994;Pennaneach and Kolodner 2009;Mackinnon and Campbell 2011;Sato et al 2012;Song et al 2013). The other is telomere addition at the broken ends; for instance, by telomerase or break-induced replication (Murnane and Sabatier 2004;Pennaneach and Kolodner 2009).…”
mentioning
confidence: 99%